Thunderbolts* : *the new Avengers [videorecording (Blu-Ray)] - Pearson, Eric, 1980-; Calo, Joanna; Pugh, Florence, 1996-; Stan, Sebastian, 1982-; Russell, Wyatt, 1986-; Kurylenko, Olga, 1979-; Pullman, Lewis, 1993-; Viswanathan, Geraldine, 1995-; Bauer, Chris; Pierce, Wendell; Harbour, David, 1975-; John-Kamen, Hannah, 1989-; et al. (Marvel Studios, 2025)
After finding themselves ensnared in a death trap set by Valentina Allegra de Fontaine, these disillusioned castoffs must embark on a dangerous mission that will force them to confront the darkest corners of their pasts. Will this dysfunctional group tear themselves apart, or find redemption and unite as something much more before it's too late?